Implementasi Kesehatan Matra sebagai Upaya Kesiapsiagaan dan Manajemen Korban dalam Penyelenggaraan Festival Musik - Darmareja, Rycco; Hasan, Melani Meta; Hermawati, Risma; Maulida, Mutia; Putri, Annisa Rahma Cahya; Alifa, Salsa Bila (Jurnal SOLMA, 2024)
Background: Organizing a music festival will cause crowds in public spaces. This condition often creates serious safety and health problems and must be of concern to organizers as a form of responsibility in anticipating fatalities and injuries due to crowds. Aim: This community service program aims to increase preparedness in the form of knowledge, attitudes, and skills of participants regarding the introduction of safety and first aid to victims during music festivals. Methode: The method used is education and training in the form of providing safety introduction education and victim aid management during music festivals. Participants consisted of 36 people from the FARINGFEST committee, Faculty of Engineering, UPN "Veteran" Jakarta. Evaluation is carried out using observation techniques and filling out questionnaires before and after the activity. Result: The results of the analysis showed that there was an increase in participant’s knowledge and attitudes after the educational program was carried out, namely 27.7% and 16.6%, with a knowledge significance of p <0.001 and p=0.002 for attitude variable. In addition, during the re-demonstration phase, participants' skills in carrying out first aid procedures for victims were also assessed as good . Conclusion: The implementation of health measures in the form of community education and training shows a significant influence on preparedness in the management of victims during music festivals. The organizing team hopes that efforts to increase the committee's preparedness will continue to be improved through various programs during the planning phase of similar public events to reduce the casualties caused.